OPTIMALISASI PENERAPAN PROSEDUR PENCEGAHAN KONTAMINASI MUATAN PADA PERGANTIAN CARGO DI MT.SAMUDERA BIRU 168 - Darmansyah Alfaruq, Revo; Mashartanto, Achmad Ali; Rizal Rochmansyah; Arifian, Naf'an; Rosnani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Cargo change operations on tanker vessels carry a risk of contamination if the tank cleaning process is not performed optimally. The problem addressed in this study is the less-than-optimal implementation of cargo contamination prevention procedures during cargo change operations on board MT SAMUDERA BIRU 168. This study aims to analyze the level of implementation of tank cleaning procedures and identify factors and constraints that influence the effectiveness of its implementation. This research employed a descriptive qualitative method using a fishbone analysis approach. Data were obtained through direct observation, interviews with officers and crew members, and ship documentation. The analysis classified potential causes into several aspects, namely human resources, work methods, equipment, supervision systems, and working environment conditions. The results show that tank cleaning procedures were generally carried out according to the established stages, from stripping to final inspection before the tanks were declared dry and up to dry. However, the implementation was not fully optimal, as indicated by flushing duration not consistently reaching 30 minutes, uneven spraying in upper frame areas, and slight moisture detected during inspection. The influencing factors include human resources, operational time pressure, hot working conditions inside the tanks